Modernizing geography teacher education through STEAM integration to enhance geoecological competence - Roza Mukhitdinova; Kuat Baymyrzayev; Murat Auyelbek (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examines the effectiveness of integrating science, technology, engineering, arts, and mathematics (STEAM) into geography teacher education to enhance geoecological competence among prospective teachers. A mixed-methods pedagogical experiment was conducted with 178 undergraduate students from two pedagogical universities in Kazakhstan, including an experimental group (n=90) and a control group (n=88). The intervention involved the integration of interdisciplinary STEAM projects, digital modeling, geographic information systems (GIS), and practice-oriented tasks focused on regional geoecological problems. Data were collected through curriculum analysis, tests, questionnaires, project evaluation, reflective reports, and expert assessment. The results revealed statistically significant improvement in the experimental group across the cognitive, activity-based, value-motivational, and reflective components of geoecological competence compared with the control group (p